ADVANCES IN LAPAROSCOPIC SURGERY: THE FUTURE OF MINIMALLY INVASIVE SURGERY FOR THE TREATMENT OF ACUTE ABDOMINAL DISEASES - Walter Ferro Schultheis, William; de Figueiredo Moutinho, Bruno; Bromonschenkel De Angeli, Daiany; Musso Rabelo, Luna; Gomes Santos, Leonardo; Marcelo Pacheco Kokis, João; Costa Fabris, Luiza; Costa dos Santos, Mariana; Barcelos Bicalho, Jhennyfer; Wagmacker Barbosa, Bárbara; Frasson Venturini, Lucas; Rebonato de Souza Ribeiro, Beatriz; et al. (Health and Society, 2024)
Laparoscopic surgery has established itself as an innovative and effective approach to treating acute abdominal diseases, revolutionizing traditional surgical practices. With the advancement of medical technologies and the growing demand for less invasive procedures, laparoscopy offers significant advantages, such as reduced postoperative pain, shorter recovery time and lower complication rates. This paper explores recent advances in the laparoscopic technique, highlighting its role in the future of minimally invasive surgery. This paper sets out to explore the main advances in laparoscopic surgery, its applications in the treatment of acute abdominal diseases and the future prospects of this minimally invasive approach, discussing how these developments can positively impact surgical practice and the patient experience. This is a literature review with a qualitative approach, using the PubMed, Google Scholar and Scielo databases. To refine the search, the health descriptors “laparoscopic surgery”, “minimally invasive surgery”, “surgical training”, and “inequalities in surgical access” were applied, with a time frame between 2020 and 2022. The methodology adopted for this analysis involves a comprehensive literature review of recent scientific articles, systematic reviews and clinical guidelines. The study examines innovations such as the use of robotics, advanced surgical instruments and improved visualization techniques, which have broadened the indications for laparoscopic surgery. In addition, the research highlights the importance of continuing education for surgeons, emphasizing the need for specific skills to successfully perform laparoscopic procedures. The data shows that laparoscopy not only improves clinical outcomes, but also promotes a more comfortable surgical experience for patients. Therefore, advances in laparoscopic surgery represent a significant milestone in the approach to acute abdominal diseases, establishing a promising future for minimally invasive surgery. The integration of new technologies and techniques, together with the proper training of professionals, is crucial to maximizing the benefits of this approach. Laparoscopy not only transforms surgical treatment, but also redefines patients’ expectations regarding recovery and quality of life. Continued development in this field promises not only better clinical results, but also a positive impact on the efficiency of health services.